Impact of Electricity Pricing Policies on Renewable Energy Investments and Carbon Emissions - Kök, A. Gürhan; Shang, Kevin; Yücel, Şafak (Management Science, 2018)
We investigate the impact of pricing policies (i.e., flat pricing versus peak pricing) on the investment levels of a utility firm in two competing energy sources (renewable and conventional), with a focus on the renewable investment level. We consider generation patterns and intermittency of solar and wind energy in relation to the electricity demand throughout a day. Industry experts generally promote peak pricing policy as it smoothens the demand and reduces inefficiencies in the supply system. We find that the same pricing policy may lead to distinct outcomes for different renewable energy sources due to their generation patterns. Specifically, flat pricing leads to a higher investment level for solar energy, and it can lead to still more investments in wind energy if a considerable amount of wind energy is generated throughout the day. We validate these results by using electricity generation and demand data of the state of Texas. We also show that flat pricing can lead to substantially lower carbon emissions and a higher consumer surplus. Finally, we explore the effect of direct (e.g., tax credit) and indirect (e.g., carbon tax) subsidies on investment levels and carbon emissions. We show that both types of subsidies generally lead to a lower emission level but that indirect subsidies may result in lower renewable energy investments. Our study suggests that reducing carbon emissions through increasing renewable energy investments requires careful attention to the pricing policy and the market characteristics of each region. This paper was accepted by Serguei Netessine, operations management.